Antropologi dan Civil Society: Pendekatan Teori Kebudayaan - Bachtiar Alam (Antropologi Indonesia, 2006)
This article seeks to demonstrate the relevance of modern anthropological perspectives to the development of civil society in Indonesia. The concept of civil society has figured prominently in the political discourses taking place in Indonesia today. It has been largely interpreted as an intermediate sphere between the state and local communities, where the discourses on individual freedom as well as cultural and religious diversity can be effectively articulated without being co-opted by the state power, or being bogged down in communal conflicts. This paper argues that modern anthropological perspectives, centering on the idea of the development of polyphonic discourses on cultural identities, can offer a powerful conceptual tool to deconstruct the cultural essentialism perpetuated by the state power and social groups, thereby making a significant contribution to the development of civil society in Indonesia. Key words: civil society; practice; discourse; culture theory.